2022-RA-1118-ESGO Pseudomyxoma peritonei arising from mature ovarian teratoma: a case report and review of current literature. (20th October 2022) - Ha, Minah; Tonga, Isileli; de Greve, Tom; Pickett, Justine
Abstract : Introduction/Background: Pseudomyxoma peritonei (PMP) is a clinical syndrome characterised by disseminated mucinous deposits within the peritoneal cavity. Majority of PMP arises from ruptured low-grade appendiceal mucinous neoplasm (LAMN). PMP arising from ovarian teratoma is a rare entity with limited case reports in the literature. Herein, we report a case of PMP arising from malignant transformation of a mature teratoma, followed by review of current literature. Methodology: Case presentation: A 57-year-old female presented to gynaecology clinic with abdominal distension and radiological findings of a large pelvic mass and large volume mucinous ascites. At laparotomy, a pre-operatively ruptured 30 cm right ovarian mucinous mass, with 20L of gelatinous mucinous ascites and mucoid material adherent to multiple peritoneal surfaces (Peritoneal Cancer Index 23) in keeping with PMP was found. An incomplete cytoreduction was performed. A high grade appendiceal-like mucinous neoplasm arising in mature teratoma was diagnosed, with positive CK7 and CK20 staining. The appendix was microscopically normal. Peritoneal mucoid deposits were found to be acellular. Recommendation was made for conservative management with no further cytoreductive surgery or hyperthermic intraperitoneal chemotherapy (HIPEC). Patient has no evidence of progression at 3 months post-surgery. Results: There are 13 published manuscripts describing PMP arising from ovarian teratoma with a total of 29 cases. Immunohistochemistry profile including CK7 and 20 appear to be variable. Most cases were treated with cytoreductive surgery, with a small number of cases having adjuvant chemotherapy or HIPEC. The risk of intra-abdominal recurrence in patients treated for PMP arising from ovarian teratoma remains unknown, however this review indicates a more favourable prognosis compared to the classic PMP from LAMN. Conclusion: PMP arising from ovarian teratoma remains a rare entity with paucity of evidence to guide optimal treatment. Prognosis is difficult to ascertain due to the lack of longitudinal follow-up data.